2012
DOI: 10.15659/yeditepemj.15.11.271
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Different Doses of Bupivacaine in Caudal Anesthesia for Neonatal Circumcision: A Randomized Clinical Trial

Abstract: Background:We aimed to compare the analgesia quality of caudal block of low volume, high concentration bupivacaine to the conventionally used volumes and concentrations of the drug in neonates undergoing circumcision with sole caudal anesthesia.Methods: Fifty neonates, undergoing circumcision were randomly assigned to low volume high concentration (group LVHC, n=25) and control groups (group C, n=25). Both groups received a caudal injection: Group LVHC 0.5 ml/kg bupivacaine 0.375% (1.875 mg/kg) and group C 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Our search generated 45 studies and in 31 of these the source of pain was a routine heel prick or venepuncture. The other pain sources were two studies involving eye examinations; three involving endotracheal or nasal suctioning; three involving oro/nasogastric tube placement; and one each involving circumcision, intubation, transurethral catheterisation, hepatitis B vaccine injection, adhesive tape removal, arterial puncture and central vein catheterisation.…”
Section: Resultsmentioning
confidence: 99%
“…Our search generated 45 studies and in 31 of these the source of pain was a routine heel prick or venepuncture. The other pain sources were two studies involving eye examinations; three involving endotracheal or nasal suctioning; three involving oro/nasogastric tube placement; and one each involving circumcision, intubation, transurethral catheterisation, hepatitis B vaccine injection, adhesive tape removal, arterial puncture and central vein catheterisation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is possible that in the light of these lower concentrations, the effective blockade is related only to sensitive fibers in function of a more slender caliber in detriment the motor fibers, while still maintaining the analgesic quality 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine is one of the most commonly used local anesthetics for caudal block and dorsal penile block and it is used in different doses and concentrations 9,10 . Adjuvant agents such as morphine, fentanyl, ketamine and neostigmine are widely used to improve the duration of effect and the quality of analgesia of the caudal block 6,11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in most studies, low complication rates have been reported for both caudal block and dorsal penile block, with no superiority of one over the other and it has been stated that both techniques could be used safely 3,4,13 . Some investigators have reported no complications or side effects in any patient who underwent caudal block 1,9,15 . Polat et al observed nausea and vomiting in 4 (14.8%) patients in the caudal block group, and in (3.3) patient in the penile block group5.…”
Section: Discussionmentioning
confidence: 99%